Time in economic theory - Zamagni, Stefano; Agliardi, E. (Cheltenham : Edward Elgar Pub., 2004)
The articles in this insightful collection attempt to provide satisfactory answers to fundamental issues on the use of time in economic theory. These volumes bring together the most important contributions on the subject, ranging from issues about the allocation of time, theory of choice, preference reversal and time in equilibrium to the issues of irreversibility, complex systems and the role of time. This comprehensive collection will be of great interest to researchers and students alike.
Includes bibliographical references and index.
oif 11/11/14
Ref
Keywords: Economics, Mathematical; Time and economic reactions; Equilibrium (Economics).; Economics